Whither Now, Opinion Modelers? - Sobkowicz, Pawel (Frontiers in Physics, 2020)
The article describes the current status and potential directions of development of Agent Based Models (ABMs) of social opinion dynamics. Despite extensive effort, the models achieve, at best, only qualitative agreement with social observations. To understand the increasingly pressing issues such as all-encompassing political and social polarization, resurgence of fundamentalist and populist movements, persistence of socially dangerous trends such as denial of climate change or the anti-vaccination activism, the models must be capable of handling much more complex set of agent characteristics, content of the communications (between agents and through media) as well as psychologically adequate reaction mechanisms and realistic influence networks. Moreover, to meet the challenge of understanding the globally growing political polarization and changes brought by increasing reliance on electronic communication the models should adapt to the post-truth era. It is necessary to include in the models phenomena such as fake news, omnipresent exaggerations and stereotypes, trolling and algorithmic biases funnelling personal information universe. We also need to consider that most social systems may be described as transient, out-of-equilibrium ones, where a crucial role is played by the models' initial conditions. In this work we analyse the challenges facing the modelling community and point out certain promising directions for development.